Peningkatan Ketersediaan Air Bersih Melalui Penerapan Teknologi Tepat Guna Di Sekolah Dasar - Sri Kusumastuti; Vinda Setya Kartika; Ilham Sayekti; Bambang Supriyo; Septiantar Tebe Nursaputro; Sidiq Syamsul Hidayat; Sheilla Nadia Valina; Devi Yesitasari; Faizah (CV. Multi Kreasi Media, 2026)
Clean water availability is a fundamental need that plays an important role in supporting educational activities, environmental hygiene, and the implementation of religious activities in schools. SD Islam Fitra Bhakti faced limited clean water supply caused by insufficient water tank capacity and an inadequately managed water distribution system. This condition disrupted sanitation activities and routine worship practices of students and teachers, particularly during peak water usage periods. This Community Service Program aimed to improve the availability and reliability of clean water supply through the application of appropriate technology that is simple, effective, and suitable for partner conditions. The implementation methods included needs assessment and analysis, technical solution design, installation of the water supply system, as well as training and assistance for school staff. The implemented solution consisted of adding water storage tanks, installing a PDAM-based water supply system, and applying an automatic stop valve to control water flow into the tank. The results indicate that the implemented system successfully increased water storage capacity and ensured a more stable continuity of clean water supply. In addition, school staff demonstrated improved understanding and independence in operating and maintaining the system after the training was conducted. The application of this appropriate technology had a positive impact on water management efficiency and supported the long-term sustainability of school operations.